2014
DOI: 10.1534/g3.114.010298
|View full text |Cite
|
Sign up to set email alerts
|

Parametric and Nonparametric Statistical Methods for Genomic Selection of Traits with Additive and Epistatic Genetic Architectures

Abstract: Parametric and nonparametric methods have been developed for purposes of predicting phenotypes. These methods are based on retrospective analyses of empirical data consisting of genotypic and phenotypic scores. Recent reports have indicated that parametric methods are unable to predict phenotypes of traits with known epistatic genetic architectures. Herein, we review parametric methods including least squares regression, ridge regression, Bayesian ridge regression, least absolute shrinkage and selection operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
189
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(208 citation statements)
references
References 101 publications
13
189
2
4
Order By: Relevance
“…Confirming the results reported by Crossa et al (2014), Howard et al (2014) found that the parametric methods studied (e.g., Bayes A, Bayes B, Bayes C, Bayes LASSO, BRR, G-BLUP, Least Squares) performed slightly better in terms of predictive ability when only additive effects were present. In the presence of epistasis, nonparametric methods (e.g., RKHS, neural networks) exceeded the parametric methods.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Confirming the results reported by Crossa et al (2014), Howard et al (2014) found that the parametric methods studied (e.g., Bayes A, Bayes B, Bayes C, Bayes LASSO, BRR, G-BLUP, Least Squares) performed slightly better in terms of predictive ability when only additive effects were present. In the presence of epistasis, nonparametric methods (e.g., RKHS, neural networks) exceeded the parametric methods.…”
Section: Discussionsupporting
confidence: 82%
“…Since Meuwissen et al (2001), many studies have compared the predictive performance of additive models in genomic selection and concluded that there is no great discrepancy among models and that when there is, it varies depending on the species and the genetic trait architecture Howard et al, 2014). However, the models tested only considered additive effects.…”
Section: Discussionmentioning
confidence: 99%
“…populations with known pedigrees (Oakey et al 2007), but marker-based estimation of epistatic effects for natural populations appears possible only with more advanced statistical methodology, for example semiparametric mixed models and reproducing kernel Hilbert spaces (Gianola and Van Kaam 2008;Howard et al 2014). Another direction for future research is the estimation of heritability in the presence of additional random effects, which would increase the applicability to agricultural field trials (where the raw data are usually at plot rather than individual plant level).…”
Section: Discussionmentioning
confidence: 99%
“…The use of semiparametric reproducing kernel Hilbert space (RKHS) regression models has been promoted as an alternative powerful option to capture epistasis in genomic selection (Gianola et al 2006;Gianola and Van Kaam 2008). The RKHS model outperformed linear models that focused exclusively on marker main effects in a number of studies based on simulated data (e.g., Gianola et al 2006;Howard et al 2014) and empirical data (e.g., Perez-Rodriguez et al 2012;Crossa et al 2013). Choosing an appropriate kernel, which can be interpreted as a relationship matrix among genotypes (i.e., individuals), is a central element of model specification in RKHS regression .…”
mentioning
confidence: 99%
“…The RKHS model outperformed linear models that focused exclusively on marker main effects in a number of studies based on simulated data (e.g., Gianola et al 2006;Howard et al 2014) and empirical data (e.g., Perez-Rodriguez et al 2012;Crossa et al 2013). Choosing an appropriate kernel, which can be interpreted as a relationship matrix among genotypes (i.e., individuals), is a central element of model specification in RKHS regression .…”
mentioning
confidence: 99%